Nutrient Deficiency Correction in Ovarian Cancer Patients Following Surgical Treatment: a Clinical Case - L. I. Bashirova; A. S. Safonov; R. R. Kamilova; D. O. Lipatov; A. A. Bakirov; A. V. Samorodov (Креативная хирургия и онкология, 2022)
Background. According to some studies, nutrient deficiencies reach an over-70% prevalence in ovarian cancer, among other gynaecological malignancies, thus constituting an important risk factor for postoperative mortality, surgical complications and longer hospital stays. Therefore, effective nutrient deficiency correction methods are warranted to improve the ovarian cancer outcomes, especially in patients following radical surgical interventions. New systematic evidence emerges in literature on the impact of such novel methods on the critical status of variant-category patients. Meanwhile, such evidence bears a recommendatory value only, with no current standard or protocol assumed for nutrient deficiency management. This issue presently remains open and requires careful research and analysis.Materials and methods. The clinical case demonstrates the efficacy of nutrient deficiency correction in an ovarian cancer patient following an individualised radical surgery.Results and discussion. The energy supplied on day 1 was >42%, >83% on day 3, and the target values had been achieved by day 7 of intensive therapy. The nutrient deficiency marker dynamics revealed the growth of transferrin, triglycerides and peripheral blood lymphocyte counts as early as by day 3 post-surgery. Albumin was the latest to respond, increasing only on day 7.Conclusion. The introduction of novel nutrition strategies and knowledge of their impact depend on further high-quality research, especially prospective studies, incorporating a  greater homogeneity of intervention types and clinical outcomes, as well as wider sampling of female ovarian cancer.